Preparation of Poly Acrylic Acid-Poly Acrylamide Composite Nanogels by Radiation Technique - Parisa Ghorbaniazar; Amir Sepehrianazar; Morteza Eskandani; Mohsen Nabi-Meibodi; Maryam Kouhsoltani; Hamed Hamishehkar (Tabriz University of Medical Sciences, 2015)
Purpose: Nanogel, a nanoparticle prepared from a cross-linked hydrophilic polymer network, has many biomedical applications. A radiation technique has recently been introduced as one of the appropriate methods for the preparation of polymeric nanogels due to its additive-free initiation and easy control procedure. Methods: We have investigated the formation of nano-sized polymeric gels, based on the radiation-induced inter- and intra-molecular cross-linking of the inter-polymer complex (IPC) of polyacrylamide (PAAm) and polyacrylic acide (PAAc). Results: The results indicated that the prepared polymeric complex composed of PAAm and PAAc was converted into nanogel by irradiation under different doses (1, 3, 5 and 7 kGy). This was due to inter- and intra-molecular cross-linking at the range of 446-930 nm as characterized by the photon correlation spectroscopy method. Increasing the irradiation dose reduced the size of nanoparticles to 3 kGy; however, the higher doses increased the size and size distribution. Scanning electron microscopy images indicated the nanogel formation in the reported size by particle size and showed the microcapsule structure of the prepared nanogels. Biocompatibility of nanogels were assessed and proved by MTT assay. Conclusion: It was concluded that low dose irradiation can be successfully applied for nanometre-ranged hydrogel.